2012
DOI: 10.1245/s10434-012-2376-5
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Node Staging for Microinvasive Breast Cancer: Is It Justified?

Abstract: Our results suggest that SLN biopsy may be justified for DCISM, but is clearly most beneficial to identify a very small subset of DCISM patients (2.7%, with SLN macrometastasis) who could benefit from systemic adjuvant therapy. The benefit of SLN biopsy for patients with SLN micrometastases/ITCs (pN0mi or pN0(i+)) is uncertain, and in these cases ALND does not appear to be warranted. We suggest a wider reappraisal of routine SLN biopsy for DCISM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 41 publications
2
24
0
1
Order By: Relevance
“…Two of the seven patients (29%) had multifocal microinvasion. All seven cases showed either intermediate (4) or high-grade (3) duct carcinoma in situ, of which three had comedo necrosis.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Two of the seven patients (29%) had multifocal microinvasion. All seven cases showed either intermediate (4) or high-grade (3) duct carcinoma in situ, of which three had comedo necrosis.…”
Section: Resultsmentioning
confidence: 98%
“…Some of the larger studies in recent years have also concluded that involvement of sentinel lymph nodes in microinvasive carcinoma is primarily in the form of isolated tumor cells and micrometastases, and additional non-sentinel axillary lymph nodes are positive only when the sentinel lymph node harbors a macrometastases. 4,[35][36][37][38] The study by Ko et al, 37 The clinical and prognostic significance of minimal tumor burden in the axilla of breast cancer patients is uncertain. As the majority of microinvasive carcinoma patients (more than 90%) harbor only isolated tumor cells and micrometastases, one might reasonably conclude that sentinel lymph node biopsy and its rigorous pathologic evaluation is an unnecessary exercise in a case of microinvasive carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing treatments of patients with DCISM in different national cancer centers, the data showed that there were less breast conserved surgery (BCS) performed in patients in Chinese cancer center than those in US patient large-volume centers (1.1% VS 47.8e68%) [20,26,27]. In addition, no significant difference of the overall survival rate between patients with DCIS and DCISM was observed after median 100 months follow-up (Fig.…”
Section: Resultsmentioning
confidence: 99%